Kesetaraan atau Hierarki?: Menafsir Peran Gender dalam Perspektif Keagamaan - Wendi Silitonga; Ayu Syahfitri; Johannes Hasibuan; Cindy Septia (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Gender inequality remains prevalent despite efforts toward equality, as traditional roles and patriarchal structures still limit women's participation and access. Resolving this requires applying egalitarian principles effectively in policies and programs. Objective: This study aims to analyze gender issues from the perspective of egalitarianism, specifically how women and men are positioned equally in social status and roles. Methods: This research uses a qualitative approach with critical discourse analysis of various gender policies, programs, and discourses in the social context. Results: four main factors reflect the egalitarian principle: (1) policies and programs must reflect the experiences of both men and women, (2) women must have access and control over programs, (3) women need to be actively involved in policy planning and implementation, and (4) it is necessary to evaluate the impact of programs on women. Conclusion: Implementing gender equality requires a legal framework and the active participation of women in all decision-making stages. Contribution: This research enriches the study of gender and public policy and provides practical recommendations for policymakers and future researchers to create a more equitable and inclusive social environment.